2020
DOI: 10.1177/0308022620945166
|View full text |Cite
|
Sign up to set email alerts
|

Activity participation patterns of community mental health consumers

Abstract: Introduction Previous international research indicates that people with severe mental illness often experience lower levels of activity participation and may therefore be marginalized from occupational opportunities that support recovery. This study aimed to describe activity and participation patterns of consumers of mental health services living in the community and identify significant relationships with demographic characteristics. Method A cross-sectional observational study design was utilized, via data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The current results guide future explorations of volitional participation and engagement, as well as the development of adherence promoting interventions that consider the pre-existing mental health status of cadets. The multidimensional relationships between Superusers, Contributors, and Lurkers regarding volitional participation in daily surveys during CTP highlights that RCMP Cadet participation does not differ from the general population ( 17 , 42 , 43 , 63 ). Lastly, cadets interact with and access the self-monitoring resources and digital social health tools in the same patterns as the general population ( 17 , 18 , 42 , 43 ).…”
Section: Discussionmentioning
confidence: 98%
“…The current results guide future explorations of volitional participation and engagement, as well as the development of adherence promoting interventions that consider the pre-existing mental health status of cadets. The multidimensional relationships between Superusers, Contributors, and Lurkers regarding volitional participation in daily surveys during CTP highlights that RCMP Cadet participation does not differ from the general population ( 17 , 42 , 43 , 63 ). Lastly, cadets interact with and access the self-monitoring resources and digital social health tools in the same patterns as the general population ( 17 , 18 , 42 , 43 ).…”
Section: Discussionmentioning
confidence: 98%
“…However, a considerable body of evidence demonstrates that consumers participate in lower levels of activity than members of the general community. An Australian study of consumers living in the community [4] found they are mostly engaged in home-based activities and unpaid work, with consumers who were older, female, and from culturally and linguistically diverse backgrounds less likely to undertake some categories of activity. Less participation by consumers is a persistent issue, having been consistently identified in research throughout the past 20 years [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Another study performed in Australia investigates activity and participation patterns among users of mental health services (Jennings et al, 2020). This quantitative cross-sectional study also sought to identify possible associations between such patterns and demographic characteristics.…”
mentioning
confidence: 99%